Paul, Scripture and Ethics. Some Reflections - Tuckett, Christopher M. 1948- (2000)
How far should one take account of the wider context of OT citations used by NT writers in interpreting a NT text? This question is addressed in this article in relation to the first readers of NT texts, and focuses in particular on two texts from 1 Corinthians. General considerations make it rather unlikely that any very broad context would have been ‘heard’ by most readers/hearers in the first century. Detailed study of 1 Cor 5.13 (with its possible allusion to exclusion formulae from Deuteronomy) suggests that no reader is likely to have picked up such an allusion. There is a stronger case for a slightly wider context having been in mind in the case of 1 Cor 1.31; but this may have been because the Corinthians themselves had the text in mind already, and this may in part explain Paul's words in 1 Cor 4.6.